2016
DOI: 10.1371/journal.pone.0156881
|View full text |Cite
|
Sign up to set email alerts
|

Refining Prescription Warning Labels Using Patient Feedback: A Qualitative Study

Abstract: The complexity of written medication information hinders patients’ understanding and leads to patient misuse of prescribed medications. Incorporating patient feedback in designing prescription warning labels (PWLs) is crucial in enhancing patient comprehension of medication warning instructions. This qualitative study explored patient feedback on five newly designed PWLs. In-depth semi-structured face-to-face interviews were conducted with 21 patients, who were 18 years and older, spoke English, and took a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Both groups agreed on the preferred location of the warning label on the medicine pack and the use of color for drawing patients’ attention. Another study by Shiyanbola et al 41 describes the outcome of a qualitative study using different variations of the five most commonly used warning labels: “Take with Food”, “Do not Drink Alcohol”, “Take with a Full glass of Water”, “Do not Chew or Break” and “Protect from Sunlight”. While appreciating the efforts, patients demanded further improvements to the content and design of the warning label to enhance clarity and understandability, 41 depicting the importance patients place on clarity of information provided through warning labels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups agreed on the preferred location of the warning label on the medicine pack and the use of color for drawing patients’ attention. Another study by Shiyanbola et al 41 describes the outcome of a qualitative study using different variations of the five most commonly used warning labels: “Take with Food”, “Do not Drink Alcohol”, “Take with a Full glass of Water”, “Do not Chew or Break” and “Protect from Sunlight”. While appreciating the efforts, patients demanded further improvements to the content and design of the warning label to enhance clarity and understandability, 41 depicting the importance patients place on clarity of information provided through warning labels.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Shiyanbola et al 41 describes the outcome of a qualitative study using different variations of the five most commonly used warning labels: “Take with Food”, “Do not Drink Alcohol”, “Take with a Full glass of Water”, “Do not Chew or Break” and “Protect from Sunlight”. While appreciating the efforts, patients demanded further improvements to the content and design of the warning label to enhance clarity and understandability, 41 depicting the importance patients place on clarity of information provided through warning labels. The same research group investigated perception on warning labels among an undeserved population and found that most rated the warning instructions to be extremely important and thought the graphics made the label information easy to understand.…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations for label improvement included: the use of bigger and bolder fonts, highlighting of warning instructions and placement on the package front. They concluded that even the redesigns proposed by the team needed further work to enhance the clarity and understandability of label information 6,7. Conclusions drawn by the Shiyanbola team are well-aligned with recommendations made by Bailey et al .…”
Section: Introductionmentioning
confidence: 60%
“…Consequently, much of the labeling information that is provided to US patients is produced by the pharmacy and regulated by the State Boards of Pharmacy. Auxiliary warnings, also called prescription warning labels (PWLs), are “small colored stickers placed adjacent [emphasis added] to the drug label on a prescription bottle” by pharmacy personnel 5,6,7,8,9. Label placement, the information contained within, and even the information relative to the specific drugs, are not uniformly standardized or required 6,10.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate use of OTC medications, even if these products are claimed to be safe for self-medication, might cause serious consequences to patients’ health [ 7 , 8 ]. However, studies have shown that patients are often confused about medication information provided by pharmaceutical companies and healthcare professionals [ 8 ], and that misinterpretation of medication information (e.g., warning label, package label and insert, and medication instruction pamphlet) is linked to medication nonadherence and misuse [ 9 , 10 ]. Thus, misunderstanding of the dosing instruction on medication packages has been cited as a critical factor that contributes to unintentional medication errors and adverse events [ 11 ].…”
Section: Introductionmentioning
confidence: 99%